The influence of pauses on the fatigue of upper limb muscles during the task of ironing - Fernandes, Ângela (2014)
The aim of this study was to analyze the influence of position and pauses on muscle activity and fatigue during the task of ironing. Ten female participants performed the task of ironing in two different positions (standing and sitting) for 10 min each with a 1-min pause at the end of each task. Muscle activity and fatigue from the upper trapezium, anterior deltoid, and pectoralis major were analyzed using surface electromyography. The results showed that the positions had no significant influence on muscle activity; nevertheless, they had significant influence on muscular fatigue. In addition, the pauses were possibly beneficial in decreasing the muscle fatigue, but the results were not conclusive.